The effect of lavender essential oil inhalation aromatherapy on students' anxiety induced by the objective structured clinical examination - Zahra Seifi; Fereidoun Jahangi; Fereidoun Jahangi; Marzieh Asadilari; Mozhgan Jokar; Sara Moghaddam; Esmaeil Kavi; Esmaeil Kavi; Mohammad-Rafi Bazrafshan (Zanjan University of Medical Sciences and Health Services, 2023)
Background & Objectives: Exam anxiety can have an unpleasant effect on students and change exam results. This study aimed to investigate the effect of inhaled lavender essential oil aromatherapy on objective structured clinical examination (OSCE)-induced anxiety. Materials & Methods: The present study was conducted as a double-blind, randomized clinical study with a control group. The participants were 51 college students who were randomly divided into two groups of placebo and intervention. The intervention group was given 2 drops of 2% lavender essential oil, and the placebo group was given 2 drops of distilled water. The samples inhaled the essential oil using an absorbable napkin attached to a face mask for 20 minutes. Before the OSCE test, each group's anxiety and vital signs were assessed and recorded before and after the intervention using the Spielberger State-Trait Anxiety Inventory (STAI) and Vital Signs Instruments. Results: The results of the independent t-test showed that before the intervention, the difference in mean anxiety between the intervention and placebo groups was not statistically significant (44.16±10.58 vs. 41.80±12.54). Even after the intervention, there was no statistically significant difference between the intervention and the placebo groups in terms of mean anxiety values (44.92±12.18 vs. 43.19±13.12). Conclusion: Inhalation aromatherapy with lavender essential oil does not affect anxiety caused by OSCE test in students.